Mindviscosity - Reynolds, Eric 1971- (Fantagraphics Books, 2020)
'Mindviscosity' is a collection of recent paintings by the artist Matt Furie, and is also his first book since 2016's beloved 'Boy's Club'. The book is a one-man bestiary of monsters, weirdos, beasts, and anthropomorphs, all painted in Furie's meticulous brand of representational surrealism. The work in 'Mindviscosity' has been created in the wake of Furie's transformative experience as the creator of Pepe the frog - a character meant to provoke joy and laughter only to be appropriated and subverted by others for genuinely sinister purposes (how that exactly happened is the subject of 'Feels Good Man', an acclaimed new feature film documentary about Furie that premiered earlier this year at the Sundance Film Festival). Furie's recent paintings seem leavened by this experience, as his unsettling menagerie of creatures seem content to withhold their true intent. Despite Furie's use of inviting colors and friendly cartoon iconography, his richly visual imagination plumbs darker depths
Keywords: Furie, Matt -- 1979-; Furie, Matt / 1979-; Painting, American / 21st century; Painting, American; Comics (Graphic works); Graphic novels; Cartoons and comics; Bildband